N-fixation in legumes – An assessment of the potential threat posed by ozone pollution. (January 2016) - Hewitt, D.K.L.; Mills, G.; Hayes, F.; Norris, D.; Coyle, M.; Wilkinson, S.; Davies, W.
Abstract: The growth, development and functioning of legumes are often significantly affected by exposure to tropospheric ozone (O3 ) pollution. However, surprisingly little is known about how leguminous Nitrogen (N) fixation responds to ozone, with a scarcity of studies addressing this question in detail. In the last decade, ozone impacts on N-fixation in soybean, cowpea, mung bean, peanut and clover have been shown for concentrations which are now commonly recorded in ambient air or are likely to occur in the near future. We provide a synthesis of the existing literature addressing this issue, and also explore the effects that may occur on an agroecosystem scale by predicting reductions in Trifolium (clovers) root nodule biomass in United Kingdom (UK) pasture based on ozone concentration data for a "high" (2006) and "average" ozone year (2008). Median 8% and 5% reductions in clover root nodule biomass in pasture across the UK were predicted for 2006 and 2008 respectively. Seasonal exposure to elevated ozone, or short-term acute concentrations >100 ppb, are sufficient to reduce N-fixation and/or impact nodulation, in a range of globally-important legumes. However, an increasing global burden of CO2, the use of artificial fertiliser, and reactive N-pollution may partially mitigate impacts of ozone on N-fixation. Highlights: Ozone-impacts on nodulation or nitrogen fixation reported in key legume species. Impacts primarily thought to result from shortfalls in carbon assimilation. >4% losses predicted in clover nodule biomass across UK pasture in typical year. Abstract : Assessing ozone effects on leguminous N-fixation.